Study on Lubricating Performance of Soft Slider Bearing in Conformal Contact. Issue 1 (1st October 2022) - Wang, Leizhen; Wang, Wen; Chen, Shangjun; Bai, Yujian
ABSTRACT: In this paper, the lubricating performance of soft slider bearing in conformal contact is analyzed. Compared with the hard slider, the soft slider will have greater elastic deformation under low pressure. Three kinds of sliders with different elastic modulus are used for comparative study in this paper. The materials of the three sliders are: steel, glass and PMMA. A hydrodynamic lubrication model of conformal contact considering elastic deformation is established according to the theory of fluid lubrication. A program for calculating dynamic pressure lubrication performance of conformal contact considering elastic deformation is developed by using Matlab and Comsol. The influence of different inclination, different speed and different load on hydrodynamic lubrication performance was studied respectively. The results show that under the same conditions, the elastic deformation on the surface of the slider is more conducive to the formation of oil film, and more conducive to the conditions of high load.